Putative RNA-directed adaptive mutations in cancer evolution. Issue 5 (19th October 2016) - Auboeuf, Didier
ABSTRACT: Understanding the molecular mechanisms behind the capacity of cancer cells to adapt to the tumor microenvironment and to anticancer therapies is a major challenge. In this context, cancer is believed to be an evolutionary process where random mutations and the selection process shape the mutational pattern and phenotype of cancer cells. This article challenges the notion of randomness of some cancer-associated mutations by describing molecular mechanisms involving stress-mediated biogenesis of mRNA-derived small RNAs able to target and increase the local mutation rate of the genomic loci they originate from. It is proposed that the probability of some mutations at specific loci could be increased in a stress-specific and RNA-depending manner. This would increase the probability of generating mutations that could alleviate stress situations, such as those triggered by anticancer drugs. Such a mechanism is made possible because tumor- and anticancer drug-associated stress situations trigger both cellular reprogramming and inflammation, which leads cancer cells to express molecular tools allowing them to "attack" and mutate their own genome in an RNA-directed manner.